Supervisor Recommendation and Final Examiner of Final Project Using Vector Space Model - Eka Pitriyani, (ReTII, 2019)
lead to unprecise and bias results. Moreover, the assigned supervisor and examiner are not matching with their expertise. Researchers have been employed vector space model to provide the objective thesis supervisor and examiner assignment. Unfortunately, the results were not formed as a rank and recommendation only for the thesis examiner. The ranking is an important form of recommendation system because will make it easy to evaluate the relevance. This study aims to use the vector space model to generate the ranking of the thesis supervisor and examiner assignment. The result shows that the function of the system performs well to generate a recommendation. The evaluation using mean average precision (MAP) with 143 queries and 1257 documents. From the evaluation, the MAP yielded a score of 0.994 and classified as an excellent recommendation based on diagnostic test. In the future, our results may be used by the thesis coordinator and students to choose and assign thesis supervisor and examiner automatically, properly and objectively. Keyword: Supervisor, Examiner, Recommendation, Thesis, Vector Space Model